Using Pakistani Literature for English Language Instruction at the Undergraduate Level at the University of the Punjab (An HEC Sponsored Project) - Dr. Rizwan Akhtar, Dr. Amra Raza & (Journal of Research in Humanities, 2023)
The present research explores various methods and strategies that can be useful in imparting English Language skills through Pakistani Literature in English to undergraduate students. The main research question focuses on the causes and hindrances that an undergraduate usually encounters in learning English especially if the learner is exposed to Language learning activities without a complimentary module of Literature. It further investigates the progress of students who have been given the opportunity to read native literary texts in English and have demonstrated more courage and creativitybased response to the learning of English Language. The research question is further substantiated through class room observations, questionnaires and interviews conducted at different departments of University of the Punjab. Literature produced by Pakistani writers is found to be a more effective and productive means of cultivating a desire and urgency for Language learning. The research also suggests that postcolonial curricula, namely of Pakistan, do not emphasise using Language and literature as a symbiotic tool of instruction therefore it is imperative to expose students to the teaching of literature produced by native writers. The findings of the present research also suggest that a reasonable frequency and magnitude of native literature will eliminate the problems of contextualization caused by canonical English texts. English Language is a global phenomenon and Pakistani Literature produced in English language also caters to an international audience.